Sistem Informasi Samsat Manokwari Berbasis Web Mengunakan Framework React: Manokwari Samsat Information System Is Web-Based Using React Framework - Leli Juliyati leli; Julius Panda Putra Naibaho Naibaho (Universitas Papua, 2024)
Leli Juliyati, Informatics Engineering Department, D3 Computer Engineering Study Program, University of Papua, January 2024 Creating a Web-Based Manokwari Samsat Information System Br, Supervised by Julius P. P. Naibaho. This paper discusses the creation of the Manokwari Samsat Information System website. The aim is to provide information and service regulations to the community. The reason for creating this website is because information is still disseminated manually by officers at the Manokwari Samsat, and residents have difficulty getting information and service rules. In this research, the author created a website using modern technology such as React, Node.js, and MySQL. The client side uses the React Framework for dynamic display, and the server side uses Node.js and RESTful API with Express.js for communication with the client. This website will help Manokwari Samsat officers serve residents better, and make it easier for residents to find out information and rules for each service.